Talking Stick Method in Mathematics Learning - Ima Hafidzah Nurhalimah; Ida Nuraida; Tika Karlina Rachmawati (Gunung Djati Conference Series, 2022)
The researcher compiled this article with the aim of explaining the talking stick method in mathematics learning. The researcher chose the literature study method to compile this article. Researchers look for several sources that have been published by previous researchers, regarding the talking stick method in learning mathematics. The researcher used sources obtained from Google Scholars with a range of publication years between 2018-2022. After the sources were collected, the researcher summarized several parts that were included in this article. The result of this research is the talking stick method is a method that can can help teachers to achieve a learning goal. The talking stick method has the advantage of improving students’ abilities in various ways